On the Convergence and Stability Results for a New General Iterative Process - Dogan, Kadri; Karakaya, Vatan (HINDAWI PUBLISHING CORPORATION, 2014)
We put forward a new general iterative process. We prove a convergence result as well as a stability result regarding this new iterative process for weak contraction operators.
Keywords: FIXED-POINT THEOREMS; Science & Technology - Other Topics